Association of "Elevated Blood Pressure" and "Stage 1 Hypertension" With Cardiovascular Mortality Among an Asian Population. Issue 8 (10 September 0207) - Talaei, Mohammad; Hosseini, Naeimeh; Koh, Angela S.; Yuan, Jian‐Min; Koh, Woon‐Puay
Abstract : Background: The new American College of Cardiology/American Heart Association high blood pressure (BP) guidelines in the United States have lowered definition of hypertension by defining normal as systolic/diastolic BP <120/80 mm Hg; elevated BP as systolic between 120 and 129 mm Hg and diastolic <80 mm Hg; and stage 1 hypertension as systolic between 130 and 139 mm Hg or diastolic between 80 and 89 mm Hg. Methods and Results: We investigated the association between the new hypertension definition and cardiovascular disease mortality among Chinese in Singapore. We used data from 30 636 participants of a population‐based cohort, the SCHS (Singapore Chinese Health Study), who had BPs measured using a standard protocol at ages 46 to 85 years between 1994 and 2005. Information on lifestyle factors was collected at recruitment (1993–1998) and follow‐up 1 interviews (1999 and 2004). Mortality was identified via nationwide registry linkage up to December 31, 2016. Neither elevated BP (hazard ratio, 0.89; 95% confidence interval, 0.74–1.07) nor stage 1 hypertension (hazard ratio, 0.94; 95% confidence interval, 0.81–1.11) was associated with increased risk of cardiovascular mortality compared with normal BP in the whole cohort. Stage 1 hypertension was associated with increased cardiovascular risk only in those <65 years of age and without a history of cardiovascular disease (hazard ratio, 1.40; 95% confidence interval, 1.01–1.94), but not in those ≥65 years of age or with a history of cardiovascular disease. Conclusions: Our data suggest that the newly defined stage 1 hypertension may not be associated with increased cardiovascular mortality across all ages among Chinese in Singapore, but that the at‐risk subpopulation is limited to those <65 years of age and without a prior cardiovascular disease.